What is evolutionary novelty? Process versus character based definitions. Issue 6 (21st June 2013) - Peterson, Tim; Müller, Gerd B.
ABSTRACT With the rise of EvoDevo, the topic of evolutionary novelty has received renewed attention. Indeed, it has been argued that one of the major contributions of EvoDevo to evolutionary theory is the explanation of phenotypic novelty. Despite such assertions, dispute continues over what exactly a novelty is and whether the term applies to a unique type of evolutionary phenomenon or whether it merely has informal meaning. In a recent special issue of J. Exp. Zool. (Mol. Dev. Evol.) dedicated to novelty, a new definition was introduced, linking novelty exclusively with adaptation and developmental constraint. In our commentary, we discuss how defining novelty in this process oriented manner leads to heightened difficulties with the application of the term and the identification of novelties. At the same time it conceals important implications for evolutionary studies. In contrast, we argue for a character based definition that is independent from adaptive necessities and promotes the integration of evolutionary factors not included in the standard theory. The implications of approaching novelty in this manner take the issue beyond definitional debates. J. Exp. Zool. (Mol. Dev. Evol.) 320B: 345–350, 2013. © 2013 Wiley Periodicals, Inc.